The Influence of Organizational Culture, Leadership, and Motivation on Performance of Early Childhood School Teachers - Kiki Setyawati (Journal of Childhood Development, 2023)
The purpose of this research is to investigate the impact of organizational culture on teacher performance; the impact of the principal's leadership on teachers' performance; motivation's impact on teachers' performance; and how motivation, principal leadership, and organizational culture affect teachers' performance. The research used a quantitative method and a questionnaire as a research instrument. Data were collected from forty-five Early Childhood School Teachers. The gathered data is then examined utilizing a quantitative approach to simple linear regression analysis and multiple linear regression analysis. The analysis's findings indicate that, with a value of 0.618 > 0.05 and a t-count value of 0.502 < t-table 2.019, the organizational culture variable had no discernible impact on teachers' performance. With a value of 0.001 < 0.05 and a t-count of 3.751 > t-table of 2.019, the principle leadership variable has a positive and substantial impact on teacher performance. With a value of 0.033 < 0.05 and a t-count of 2.208 > t-table of 2.019, the motivating variable has a positive and significant impact. With a significance level of 0.000 < 0.05 and an f-count value of 30.968 > f-table 2.83, the factors organizational culture, principle leadership, and motivation have a significant and simultaneous impact on teacher performance